A Study and Characterization of Zn-DOPED NiO nanoparticles using Wet chemical method (International Journal of Food and Nutritional Sciences, 2022)
In present study, the synthesis of illustrated that wet chemical reduction method is an applicable way for synthesis of Zn doped NiO nanoparticles. X-ray diffraction patterns of the nickel nanoparticles prepared with water , propanaol and ethanol on different concentrations of hydrazine confirm that the peaks are well defined and agree well with the JCPDS data of cubic structure.. SEM images of the zinc doped nickeloxide nanoparticles shows that shape of the particles is nearly spherical with homogeneous size distribution. It is observed from the EDAX analysis that the average atomic and weight percentage of Nickel oxide nanoparticles exhibits nearly the composition without inclusion of any other impurities in each case. The FT-IR spectra indicated the formation of Zinc doped Nickel Oxide nanoparticles. The chemical structure information of the products is studied by FTIR spectra. An absorption spectra of ethanol and ethanol assisted Zn-doped NiO samples with the strong absorption edges in obtained from the UV region at 350 and 310 nm, respectively.